Finding dignity at the end of life : a spiritual reflection on palliative care - Benton, Kathleen; Pegoraro, Renzo (New York, NY : Routledge, 2020)
"Finding Dignity at the End of Life discusses the need for palliative care as a human right and explores a whole-person methodology for use in treatment. Mental health practitioners, allied professionals, and theologians will find this a useful and reflective guide to palliative care and its connection to faith, spirituality, and culture"--
OCLC-licensed vendor bibliographic record.
Keywords: Palliative treatment -- Religious aspects; Terminal care -- Religious aspects; Dignity